An appeal, written by William J. Maloney, "to the American public" to support the work of the American Committee for Relief in Ireland, - Maloney, William Joseph Marie Alois, b. 1881 (1920)
Maloney suggests that the Organisation of the Committee should be called the "Irish Red Cross (American Branch) in Ireland", and details how the Committee should be organised by state in the United States.